Fluctuations in the emotional intelligence of therapy students during clinical placements: Implication for educators, supervisors, and students. Issue 1 (2nd January 2017) - Gribble, Nigel; Ladyshewsky, Richard K.; Parsons, Richard
ABSTRACT: This study investigated the changes in emotional intelligence (EI) of occupational therapy, physiotherapy, and speech pathology students (therapy students). Clinical placements have multiple benefits including the development of interprofessional skills, enhancing practice skills and interpersonal skills. Higher EI competencies have been shown to have a positive impact on patient outcomes, teamwork skills, dealing with stress, and patient satisfaction. Data for this study were collected at two time points: before third-year therapy students commenced extended clinical placements (T1 with 261 students) and approximately 7 months later after students had completed one or more clinical placements (T2 with 109 students). EI was measured using the Emotional Quotient Inventory 2.0 (EQ-i 2.0 ). Only one EI score, assertiveness, demonstrated a significant decline. No EI score showed a significant increase. A third or more of the students showed increases of five points or more in self-actualisation, emotional expression, independence, reality testing and optimism. However, of concern were the five EI scores where therapy students' EI scores decreased by more than five points: assertiveness (where 38% of students declined), problem solving (37%), impulse control (35%), self-actualisation (35%), and stress tolerance (33%). With EI scores declining for some students during clinical placements, there are implications for clinical supervisors and interprofessional facilitators as clinical performance may decline concurrently. There is a range of potential reasons that clinical placements could negatively influence the EI competencies of a therapy student, including poor clinical supervision, conflict between a student, and supervisor and failing a clinical placement. The research suggests that interprofessional facilitators and university educators might consider students undertaking EI tests before clinical placements.